Fever from Primary Tooth Eruption: What is the evidence? - Matos,Sara (2018)
Introduction: There is no consensus on the causal relationship between primary dental eruption and both systemic and local signs and symptoms. Fever, an important sign, is often reported. Such lack of evidence hampers clinical reasoning and may contribute to delayed diagnosis of important conditions. Objective: To review existing evidence underlying the association between primary tooth eruption and fever. Methods: A review of the evidence on English, Portuguese and Spanish scientific publications over the last ten years was performed in the main international databases using the query tooth eruption and fever [MeSH], and in the index of Portuguese medical journals using the query erupção dentária and febre [DeCS]. SORT system of the American Family Physician was used for rating the strength of evidence. Results: A total of 53 articles were retrieved, from which two meta-analyses and two original studies were selected, comprising a total of 5317 children. Massignan et al. (2016) meta-analysis and Memarpour et al. (2015) clinical trial found a slight temperature increase on the day of primary tooth eruption, but no fever. In Nemezio et al. (2017) meta-analysis, this association was observed in the subgroup that used the rectal method for temperature assessment. Un Lam et al. (2016) observational study reported a fever prevalence of 49.9%. Discussion and conclusions: The present analysis had several limitations, including a significant heterogeneity amongst studies in the definition of fever, interpersonal variability during fever measurements, different fever assessment methods or absence of that information, and no exclusion of confounding factors. Given available evidence, it is not possible to establish a clear association between primary dental eruption and the occurrence of fever. A higher number of robust studies is required to confirm this hypothesis (SORT B).